(3fgL GdMb hcTa GdUObs - (3GdMSf (B- (3hjbGd(B: (3GdMSjf (B- (3Hf jhSa GHf Ydj Hf GdeWgQ GdMdj, LeGd GdOjf,J (B726 (3g` s
(3ChdgG (B:s
(3CeG HYO aEf Gddg JYGdi MjK MQe ai cJGHg GdYRjR cJeGf BjGJg s
(3BNQgG (B:s
(3EfeG GYJbOhG eG GYJbOhg ef GdYbGFO GdHGWdI WdHkG ddefGaY GdOfjhjI Je GdcJGH hGdMeO ddg QH GdYGdejf hUdhGJg Ydi SjOfG eMeO hBdg GdWGgQjf s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B693s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
Keywords: (3GdJhMjO hGdedd hGdfMds